2019
DOI: 10.1111/jbg.12419
|View full text |Cite
|
Sign up to set email alerts
|

Significance testing and genomic inflation factor using high‐density genotypes or whole‐genome sequence data

Abstract: Significance testing for genome‐wide association study (GWAS) with increasing SNP density up to whole‐genome sequence data (WGS) is not straightforward, because of strong LD between SNP and population stratification. Therefore, the objective of this study was to investigate genomic control and different significance testing procedures using data from a commercial pig breeding scheme. A GWAS was performed in GCTA with data of 4,964 Large White pigs using medium density, high density or imputed whole‐genome sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 40 publications
(46 reference statements)
1
31
0
Order By: Relevance
“…It has been widely observed that RA and SLE have common pathological and clinical features (Manoussakis et al, 2004;Icen et al, 2009;Orozco et al, 2011;Toro-Domínguez et al, 2014;Márquez et al, 2017;Acosta-Herrera et al, 2019), which are partly attributable to common genetic foundation between the two diseases. However, the genetic overlap underlying RA and SLE remains elusive and a large proportion of genes related to them are yet not discovered (Ramos et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been widely observed that RA and SLE have common pathological and clinical features (Manoussakis et al, 2004;Icen et al, 2009;Orozco et al, 2011;Toro-Domínguez et al, 2014;Márquez et al, 2017;Acosta-Herrera et al, 2019), which are partly attributable to common genetic foundation between the two diseases. However, the genetic overlap underlying RA and SLE remains elusive and a large proportion of genes related to them are yet not discovered (Ramos et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The objective of our study was to gain insight into genetic mechanism linking between RA and SLE using advanced bioinformatics approaches. By leveraging publicly available GWAS summary statistics, we identified a significant positive genetic correlation between RA and SLE, indicating that genetic variants associated with the risk of SLE would be also related to the risk of RA, or vice versa (Icen et al, 2009;Toro-Domínguez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomic inflation factor expresses the deviation of the distribution of the observed test statistic compared to the distribution of the expected test statistic. High genomic inflation factors are caused by population stratification, strong linkage disequilibrium (LD) between SNPs, strong association between SNPs and phenotypes, and systematic bias [32].…”
Section: Discussionmentioning
confidence: 99%
“…For a trait with a low heritability, the threshold value for significance of associating loci with a trait would have low −log10 (p-values) [33]. In published studies in pig populations, threshold values for −log10 (p-value) ranged from 3.3 to 6, using either no multiple testing correction, a Bonferroni correction, the false discovery rate, or genomic control [32].…”
Section: Discussionmentioning
confidence: 99%